Pengambilan Keputusan Strategis di Perusahaan Startup - N, Rusdi Hidayat; Kusumasari, Indah Respati; Latifah, Narulika Ris; Girsang, Viola Natalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the strategic decision making process in startup companies using a descriptive qualitative approach. This approach was chosen to explore in depth the phenomenon of strategic decision making through comprehensive data collection. The research results show that internal factors, such as the characteristics of the founding team, greatly influence the quality of strategic decisions. Teams with diverse industry experience tend to make more comprehensive and successfully implemented decisions. From an external perspective, market dynamics, industry competition, as well as macroeconomic and regulatory conditions influence startup strategic decisions, especially in facing market uncertainty. This research suggests that systematic integration of customer feedback and effective implementation of innovation need to use a holistic approach to improve the quality of strategic decisions in startups, especially in the face of uncertainty and intense competition.